Response of equatorial, low- and mid-latitude F-region in the American sector during the intense geomagnetic storm on 24–25 October 2011 - de Jesus, R. (2013)
In this paper, we present and discuss the response of the ionospheric F-region in the American sector during the intense geomagnetic storm which occurred on 24–25 October 2011. In this investigation ionospheric sounding data obtained of 23, 24, 25, and 26 October 2011 at Puerto Rico (United States), Jicamarca (Peru), Palmas, Sa˜o Jose´ dos Campos (Brazil), and Port Stanley, are presented. Also, the GPS observations obtained at 12 stations in the equatorial, low-, mid- and high-mid-latitude regions in the American sector are presented. During the fast decrease of Dst (about 54 nT/h between 23:00 and 01:00 UT) on the night of 24–25 October (main phase), there is a prompt penetration of electric field of magnetospheric origin resulting an unusual uplifting of the F region at equatorial stations. On the night of 24–25 October 2011 (recovery phase) equatorial, low- and mid-latitude stations show h0 F variations much larger than the average variations possibly associated with traveling ionospheric disturbances (TIDs) caused by Joule heating at high latitudes. The foF2 variations at mid-latitude stations and the GPS-VTEC observations at mid- and low-latitude stations show a positive ionospheric storm on the night of 24–25 October, possibly due to changes in the large-scale wind circulation. The foF2 observations at mid-latitude station and the GPS-VTEC observations at mid- and high-mid-latitude stations show a negative ionospheric storm on the night of 24–25 October, probably associated with an increase in the density of molecular nitrogen. During the daytime on 25 October, the variations in foF2 at mid-latitude stations show large negative ionospheric storm, possibly due to changes in the O/N2 ratio. On the night of 24–25, ionospheric plasma bubbles (equatorial irregularities that extended to the low- and mid-latitude regions) are observed at equatorial, lowand mid-latitude stations. Also, on the night of 25–26, ionospheric plasma bubbles are observed at equatorial and low-latitude regions.